Jews at Williams : Inclusion, Exclusion, and Class at a New England Liberal Arts College - Wurgaft, Benjamin Aldes (Book collections on Project MUSE., 2013)
A study of anti-Semitism, assimilation, and class--the forces that governed Jewish participation in elite higher education for the first two-thirds of the twentieth century.